Exploration of self-care practices from coping strategies perspective among trainee counsellors - Merikan Aren; Waheeda Pisal (Education and Social Sciences Review, 2022)
Self-care practices regarded as one of the most important components for the profession of counselling. Besides, self-care practices are also recognized as an essential necessity for trainee counsellors in becoming helping professionals in future. Nonetheless, there is insignificant in previous studies regarding self-care practices among trainee counsellors. The purpose of this study is to explore self-care practices from a coping style perspective among trainee counsellors. This study adopted a descriptive qualitative research design in exploring the self-care practices among trainee counsellors at one of the universities in Sarawak, Malaysia using Six Part Story Method. The application of Six Part Story Method helps in exploring the self-care practices by illustrating the drawing through the six boxes. The data was collected through group counselling sessions and data was analyzed using the BASIC Ph Model. Overall, six themes have emerged from the findings. The results from these findings shows that trainee counsellors are highly dominant in Social and Physical Dimensions. Besides that, this study also proposes on determining the suitability of Six Part Story Method in counselling approach. This study has contributed to the existing knowledge on the self-care practice in context of trainee counsellors. It enhances awareness to the society especially people in counselling field on the importance of practicing self- care when experiencing stressful circumstances.